2001
DOI: 10.1002/1521-3773(20010302)40:5<850::aid-anie850>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Fronts, Waves, and Stationary Patterns in Electrochemical Systems

Abstract: Oscillatory behavior has been observed for almost all electrochemical reactions in a certain, although sometimes small, range of external parameters. Only in the past ten years has it been possible, however, to find a common explanation for the occurrence of these temporal self‐organization phenomena of chemically completely different electrochemical reactions. The breakthrough was achieved because new methods and concepts, which had been developed in nonlinear dynamics to describe the spontaneous formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 57 publications
0
36
0
1
Order By: Relevance
“…The notable circumstance that experimental patterns found in electrodeposition processes exhibit structures that are strongly reminiscent of those found in many different natural systems (such as fish and animal coat markings, sand dunes, grass landscapes) has suggested that such experimental electrochemical scenarios could be explained within the reaction-diffusion modelling framework [40,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notable circumstance that experimental patterns found in electrodeposition processes exhibit structures that are strongly reminiscent of those found in many different natural systems (such as fish and animal coat markings, sand dunes, grass landscapes) has suggested that such experimental electrochemical scenarios could be explained within the reaction-diffusion modelling framework [40,45].…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical modelling of electrochemical dynamics and of the related pattern formation processes has been mainly developed for variants of the activator-inhibitor mechanism and focused on electrocatalysis [36,40,45] more than electrodeposition. Nevertheless, in this field experimental pattern formation has been observed in a series of experiments regarding, among others, Ag [27,38], Co-In [39] and Ni-P-W-Bi [15] alloys.…”
Section: Introductionmentioning
confidence: 99%
“…2 nm apart. At such large interatomic distance, interactions between the redox centers will be minimal, thus the rapidity of the phase change is likely caused by the presence of negative differential resistance leading to bistability within the electrochemical system (21).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Electrochemistry is an ideal playground for the study of dynamic instabilities because here most experiments are carried out under conditions far from thermodynamic equilibrium. It is therefore not surprising that the majority of known bistable, oscillating, and chaotic reactions is found in electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The range and the strength of this spatial coupling are determined by parameters such as the cell geometry, the external resistance, and the conductivity of the electrolyte. 10 In many standard electrochemical applications, the setup creates strong, long-range coupling through the electrolyte, which hampers the formation of pronounced spatial patterns. For the case of weak, long-range coupling, however, complex spatiotemporal oscillations [11][12][13][14] as well as accelerating 15 and "remote-triggered" fronts 16 have been observed.…”
Section: Introductionmentioning
confidence: 99%